Art studies aspects of the research of modern kazakh tapestry. (Eurasian Journal of Philology Science and Education, 2015)
This article discusses the major landmarks in the art history to explore the phenomenon of the development of the Kazakh auteur art of tapestry in the space of the world culture. It also analyzes the art studies works devoted to the research of various aspects of the development of the art of tapestry in Europe, the former USSR countries, the CIS and Kazakhstan. According to the author, modern artists should keep a relentless search for new technological methods, unusual art-style solutions in the spirit of modern aesthetics, as well as for interesting and memorable visual images that reveal the philosophical, ethnographic and historical aspects of life of the Kazakh nation in the past, present and future.
Keywords: аrt studies; contemporary tapestry; Kazakhstan; art textile